Explorando o engajamento, independência e relações sociais em rotinas da educação infantil - Moro, Gabrielle (Universidade Federal de São Carlos, 2025)
Child development is a multifaceted process involving motor, cognitive, emotional, and social aspects, strongly influenced by family and school interactions. Children's active participation in early childhood education routines is essential to promote engagement, independence, and social skills. However, poorly accessible school settings can limit this participation, especially among children with atypical development. The adoption of inclusive pedagogical practices and the importance of early intervention emerge as ways to increase children's participation and leadership in school routines. OBJECTIVES: To analyze and compare the engagement, independence, and social relationships of 4- to 6-year-old children, with and without atypical development, in early childhood education routines. The research also seeks to support more inclusive pedagogical practices and reinforce the importance of early intervention in the school environment. METHODOLOGY: This is a quantitative study conducted with teachers and guardians of 4- to 6-year-old children at an Early Childhood Education institution at UFSCar. Two instruments were administered: a characterization questionnaire and the ClaMEISR (Classroom Measure of Engagement, Independence, and Social Relationships) by R.A. McWilliam (2014) and translated and adapted into Brazilian Portuguese by Barros and Della Barba (2019), completed by the teachers. The data were organized, statistically analyzed, and discussed based on the domains of engagement, independence, and social relationships. RESULTS: The data revealed that 5-year-olds had higher averages in all three domains assessed, compared to 4-year-olds. Children with typical development also obtained higher scores compared to atypical children, especially in routines requiring greater social initiative. Structured and mediated routines were more inclusive, while symbolic routines showed greater disparity in participation. The ClaMEISR proved effective in identifying patterns of participation and guiding pedagogical interventions.
Exploring engagement, independence and social relationships in early childhood education routines
Keywords: Engajamento nas rotinas; intervenção precoce; educação infantil; autonomia; relações sociais; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 4. Educação de Qualidade